Metaphorical Euphemisms in Dholuo Marriage Conflict Resolution Program ‘Dak Man Gi Ndhadhu’ on Radio Nam Lolwe - Owino, Felix; Mudogo, Benard; Miriti, Gervasio (Journal of Pragmatics Research, 2026)
This paper investigates the Marriage Conflict Resolution (MCR) discourse among Dholuo speakers, which is full of taboo words, particularly those with sexual connotations and other obscenities. The purpose is to examine the use of metaphorical euphemisms by interlocutors to enhance the comprehension of ideas and to politely avoid taboos for culturally acceptable communicative purposes. The study employs a cognitive linguistics approach to analyze these metaphorical euphemisms. Using a descriptive research design, data are collected through Key Informant Interviews and a digital corpus from the Dholuo marriage conflict resolution program Dak Man Gi Ndhadhu on Radio Nam Lolwe, a vernacular station for Dholuo speakers broadcasting in Kisumu County, Kenya. The Metaphor Identification Procedure Vrije Universiteit (MIPVU) is employed to interrogate whether the expressions and lexical items identified are metaphorical. The items are then transcribed and translated into English.The study findings show that MCR metaphorical euphemisms are conceptualized through the interlocutors’ experiences, such as actions, organisms, food, body parts, journeys, objects, human beings, and nature. The findings indicate that Dholuo speakers effectively apply their understanding of these concepts to enhance their comprehension of marital issues. The study focuses solely on the cognitive-linguistic processes underlying metaphorical euphemism and not on gender-based perspectives. The study concludes that Dholuo speakers conceptualize MCR issues through metaphorical euphemisms to avoid taboo language.